The Relationship of Husband's Knowledge, Attitude, and Support to Low Interest in Use of IUD Contraceptive Methods in Work Area Community Health Center Technical Implementation Unit Melak - Asmiranti, Novita; Parellangi, Andi; Imelda, Fara (Jurnal KESANS : Kesehatan dan Sains, 2023)
Introduction: The use of contraceptives at the Melak Health Center is still dominated by short-term contraceptives, while the level of use of long-term contraceptive methods, especially the IUD is still low. Melak Health Center wheres has made efforts to increase interest in the use of IUDs such as providing counseling to WUS and cross-sectoral cooperation. Objective: The purpose of this study was to determine the relationship between knowledge, attitudes and husband's support for the low interest in using the IUD contraceptive method in the Technical Implementation Unit working area Malacca Health Center.  Methods: This type of research is an analytic survey using a cross sectional design.  Results: The characteristics of most wives are between 31-40 years old (48.8%), high school education (36.9%) and household members (47.6%). The research variables were mostly poor knowledge about IUD (64.3%), negative attitude towards IUD (54.8%), husband was less supportive (60.7%) and less interested in using the IUD contraceptive method (58.3%).  Discussion: Knowledge is not good due to lack seeking information such as from mass media. Negative attitude is due to perception that IUD is less safe to prevent pregnancy, costs more and interferes with husband & wife relationships. Husbands are less supportive because they do not provide funds or do not deliver to IUD services. Conclusion: Husband's knowledge, attitude and support associated with low interest in using the IUD.